Analysis of VH-CATT EHL Minimum Film Thickness in Meshing Process - Pei Luo; Li Hou; Yang Wu; Yangzhen Ji; Xubing Liu; Yongqiao Wei (Jixie chuandong)
Based on the tooth surface equation of the Variable hyperbolic circular-arc-tooth-trace （VH-CATT）， the gear meshing principle is used to analyze the tooth surface contact during the meshing process， the positions distribution of the VH-CATT meshing point during meshing process of the concave and convex tooth surface is obtained. According to the principles of gear geometry， the formulas for calculating the important parameters of EHL such as the principal curvatures and entrainment velocity of the VH-CATT meshing point during meshing process of the concave and convex tooth surface is obtained. The Downson-Higginson minimum film thickness model is used to analyze the minimum film thickness of EHL in the VH-CATT meshing process， and the variation rules of EHL minimum film thickness in the meshing process of gear pairs with different gear design parameters are obtained. Theoretical analysis shows that the lubrication condition between the dedendum of driver gear （the concave tooth surface） and the addendum of driven gear （the convex tooth surface） of VH-CATT is the worst， where the wear failure of tooth surface is most likely to occur. When the input load increases， the minimum film thickness decreases slightly， and the gear is provided with the characteristics of impact load resistance. With the increase of pressure angle， the minimum film thickness increases so that the lubricity and bearing capacity are improved. When the tooth trace radius becomes longer， the minimum film thickness decreases slightly， selecting a reasonable cutter head radius to process the gear can improve the lubricity. The results provide a theoretical basis for the lubrication design and wear calculation of VH-CATT.